Produção de energia elétrica e carvão ativado a partir de um gaseificador de biomassa - Freitas, Merques do Nascimento (2019)
Gasification is the most efficiency process to extract chemical energy from biomass. It has been proved to be a great promise to generate electricity at low cost without damaging the environment. Much research in this area has been done to improve the technology in order to make it affordable to the communities. In this work it is discussed the possibility of generating electricity, as well as to produce charcoal having high superficial area, using a biomass gasifier coupled with a genset. The gasifier having an 8 kW thermal capacity was connected to an 18 hp Otto cycle engine (VANGUARD V-Twin) adapted to run with poor gas, and to a TOYAMA generator having 2 kW nominal power; a resistivity simulator as well as several instruments. An ash removal device serving also to extract pieces of charcoal was implemented on the gasifier. The results show that the specific consumption of biomass (kg/kW.h) decreases as the electrical power rises; the efficiency of the system gasifier/genset is directly proportional to the electrical power generation; the content of fixed carbon on the charcoal went from 65,22 % to 70,86 %. Gasification process shown to be an economic alternative to generate electricity, as well as to produce charcoal having significant superficial area high fixed carbon.